Conceptual Model of Providing Traffic Navigation Services to Visually Impaired Persons - Periša, Marko; Peraković, Dragan; Šarić, Slavko (Promet - Traffic&Transportation, 2014)
In order to include people of reduced mobility in the traffic system it is necessary to provide accessibility and information of the users to all the facilities surrounding them. By analysing the currently available information and communication technologies a new conceptual model of providing navigation services to the visually impaired persons has been proposed. This model is based on Cloud Computing platform, and this research describes the method of navigating the users based on accurate and updated data. The users’ requirements have been analysed according to the needs of the movement of visually impaired persons along the traffic network. The information and communication solutions with the function of informing these groups of users have to provide accurate and updated data, which is made possible by the proposed model. This research was conducted on the most frequent routes in the city of Zagreb. With the review of model efficiency user’s sense of security is increased in the amount of 87%.